Performance Characteristics of a Quantitative TaqMan Hepatitis C Virus RNA Analyte-Specific Reagent - Barbeau, James M. (American Society for Microbiology, 2004)
We determined the dynamic range, reproducibility, accuracy, genotype bias, and sensitivity of the TaqMan hepatitis C virus (HCV) analyte-specific reagent (ASR). Serum samples were processed using the MagNA Pure LC instrument and run on the COBAS TaqMan 48 analyzer. The performance characteristics of the ASR were also compared with those of the qualitative AMPLICOR and quantitative AMPLICOR MONITOR HCV tests. The ASR exhibited a ≥6-log(10) linear dynamic range and excellent reproducibility, with a mean coefficient of variation of 14%. HCV RNA concentration measured with the ASR agreed within an average of 0.42 log(10) (2.6-fold) of the labeled concentration with members of a standard reference panel. HCV genotypes 1 to 4 were amplified with similar efficiencies with the ASR. The ASR and AMPLICOR MONITOR viral load results were significantly correlated (r = 0.8898; P < 0.01), but the agreement was poor (mean difference, 0.45 ± 0.35 log(10)) for 72 HCV RNA-positive clinical samples. However, 98.9% agreement between the ASR and qualitative AMPLICOR test results was found with 60 positive and 29 negative samples. Limiting-dilution experiments demonstrated that the limits of detection for ASR and AMPLICOR tests were 84 and 26 IU/ml, respectively. The performance characteristics of the TaqMan HCV ASR are appropriate for all clinical applications of HCV RNA testing.